Effect of Dietary Amylose/Amylopectin Ratio on Intestinal Health and Cecal Microbes’ Profiles of Weaned Pigs Undergoing Feed Transition or Challenged With Escherichia coli Lipopolysaccharide - Yang, Can; Wang, Min; Tang, XiaoWu; Yang, HuanSheng; Li, FengNa; Wang, YanCan; Li, Jianzhong; Yin, YuLong (Frontiers in Microbiology, 2021)
Background: Dietary amylose/amylopectin ratio (DAR) plays important role in piglets’ intestinal health. It is controversial whether diarrhea could be relieved by changing DAR in weaning piglets. Methods: Sixty (Landrace × Yorkshire) castrated male pigs (initial body weight 6.51 ± 0.64 kg) were allotted to 5 groups (1 pig/cage and 12 replicates/group) in a randomized complete block design according to their BW. Piglets were fed ad libitum with diets different in DAR (0.00, 0.20, 0.40, 0.60, 0.80) for 29 days. Feed transition occurs at day 15. The piglets were challenged with lipopolysaccharides (100 μg/kg BW) on day 29 by intraperitoneal injection at 12 h before slaughter. Chyme was collected for pH value, volatile fatty acid and intestinal flora analysis using 16S rRNA gene sequencing. Results: Diarrhea rate and diarrhea degree were higher when DAR was 0.40 than 0.20 and 0.80 during third week (P<0.05). Cecal pH value was higher (P<0.05) in 0.20 than in 0.00 and 0.80, but with no significant difference compared with 0.40 and 0.60 (P>0.05). Cecal isobutyric acid and iso-Valeric acid was higher in 0.20 than other groups (P＜0.01).Cecal acetic acid, propionic acid and total short chain fatty acid (SCFA) concentration were higher in group 0.40 than 0.00, 0.60, 0.80 (P＜0.05),but with no significant difference compared with 0.20 (P>0.05). Cecal crypt depth was lower (P＜0.05) in 0.80 than in other groups but not 0.40. Claudin mRNA expression in the mucosa of the ileum was higher in 0.20 than in other groups (P＜0.01). Alpha diversity of cecal microbial representative by goods coverage was higher in group 0.40 when compared with group 0.20 (P＜0.05). At the genus level, abundance of Ruminococcaceae_ NK4A214_ group and Anaerotruncus were higher but Cetobacterium was lower in cecal chyme of group 0.20 than that in group 0.60 (P<0.05), with no significant difference compared with other groups (P>0.05). Diarrhea rate during third week was negatively correlated with abundance of Rikenellaceae_RC9_ gut_ group and X.Eubacterium_coprostanoligenes_group (P<0.05). Conclusions: Diarrhea occurred when weaned piglets received diet with DAR 0.40 during feed transition, but they will regulate cecal microorganism and metabolites to restore their health.